Health of adults living with a clinically significant haemoglobinopathy in New South Wales, Australia. Issue 10 (18th October 2013) - Crowther, H. J.; Lindeman, R.; Ho, P. J.; Allen, E.; Waite, C.; Matthews, S.; Jobburn, K.; Teo, J.; Day, S.; Seldon, M.; Rosenfeld, D.; Kerridge, I.
Abstract Aim To comprehensively review the health needs of patients living with clinically significant haemoglobinopathies (thalassaemia and sickle‐cell disease (SCD)) in New South Wales, Australia. Methods A survey‐based health needs assessment was undertaken in outpatients cared for at five tertiary institutions in metropolitan and regional centres. Sixty‐three of 121 adults (approximately 80–90% of adult patients with transfusion‐requiring haemoglobinopathies in New South Wales) completed an in‐house and commercial health‐related quality assessment survey (SF‐36v2). Results Subjects came from more than eight world regions, with those with SCD being more likely to be born outside of Australia than subjects with thalassaemia (P < 0.001, likelihood ratio 20.64) as well as more likely to have been refugees (26% vs 2%). The population contained socially disadvantaged subjects with 13 subjects (20.6%) having incomes below the Australian poverty line. Complications of thalassaemia were comparable to previous international reports although our subjects had a high rate of secondary amenorrhea (>12 months = 27%) and surgical splenectomy (55.6%). Use of hydroxyurea in SCD was less than expected with only 46.6% of subjects having prior use. Lack of universal access to magnetic resonance imaging‐guided chelation (international best practice) was evident, although 65.5% had been able to access magnetic resonance imaging through clinical trial, or self‐funding. Conclusions Patients with SCD and thalassaemia experience considerable morbidity and mortality and require complex, multidisciplinary care. This study revealed both variance from international best practice and between specialist units. The results of this research may provide the impetus for the development of clinical and research networks to enable the uniform delivery of health services benchmarked against international standards.